Current Update of Primary Angle Closure Glaucoma - Widya Artini (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Primary angle closure glaucoma is the most leading caused of permanent blindness among glaucoma patients.Â We will describe up dated primary angle closure group management to resolved this devastated diseased. First step, a prompt diagnostic is a must, then laser peripheral iridotomy should be done. If the angle was found closed after LPI less than 1800, and intra ocular pressure increases more than 21 mmHg, the management should be followed by glaucoma medication or lens extraction. If the angle was closed more than 1800, more aggressive treatment is recommended, such as lens extraction, trabeculectomy or combined. Clear lens extraction as an early treatment is suggested in many eye centers, even though is it still controversial issue.